Is a more exciting LaLiga possible? - Pic, M.; García-Díaz , PR (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The ranking of LaLiga championship for the 2008/09 season was one of the poorest ever in terms of uncertainty. The main aim of this study is to stimulate public interest in the Spanish League championship. To achieve this, an alternative ranking system is proposed using variables derived from soccer’s internal logic and the quality of the various teams. Applying Kendall’s index of concordance, the two rankings were compared play by play demonstrating the viability of the new model, with different levels of competitiveness. The properties and limitations of the model were compared with the one currently used by LaLiga. Providing a process which makes allowances for the wide range of quality of the teams playing in LaLiga is an alternative intended to foment the competitiveness of the championship.